PENGARUH BIAYA PRODUKSI DAN HARGA JUAL TERHADAP PENDAPATAN PETANI DALAM PERSPEKTIF EKONOMI SYARI’AH (Studi Pada Petani Jagung Desa Sidoharjo Kecamatan Jati Agung Lampung Selatan) - Agata Omayda, Walke Agnola Faustine (UNISAN JURNAL, 2024)
This study aims to analyze and explain the effect of production costs and selling prices on the income of corn farmers in Sidoharjo Village, Jati Agung District, South Lampung Regency. The data collection method used in this study is a questionnaire with a Likert scale. The study population includes all corn farmers in the village, totaling 2,489 households, with a sample size of 96 corn-farming households. The data analysis techniques applied in this study include classical assumption tests and multiple regression analysis. The results of the study indicate that the production cost variable has a t-value greater than the t-table value (3.331 > 1.661) with a significance level of 0.001 < 0.05. Meanwhile, the selling price variable also has a t-value greater than the t-table value (2.238 > 1.661). This shows that, partially, production costs (X1) and selling prices (X2) have a significant effect on income (Y). Based on the simultaneous test (F-test), the F-value obtained is 16.528, which is greater than the F-table value (3.09), with a significance level of 0.000 < 0.05. These results indicate that production costs (X1) and selling prices (X2) together have a significant impact on income (Y). Meanwhile, the coefficient of determination (R²) of 0.262 suggests that the independent variables in this study influence the dependent variable by 26.2%, while the remaining 73.8% is affected by other factors not examined in this study